Repression of Hyphal Proteinase Expression by the Mitogen-Activated Protein (MAP) Kinase Phosphatase Cpp1p of Candida albicans Is Independent of the MAP Kinase Cek1p - Schröppel, Klaus (American Society for Microbiology, 2000)
Cpp1p is a putative mitogen-activated protein (MAP) kinase phosphatase that suppresses Candida albicans hyphal formation at 25°C through its probable substrate, the Cek1p filamentation MAP kinase. Here we report that expression of the serum-induced genes SAP4-6 and HYR1 increased several fold in hyphal forms of a cpp1/cpp1 null mutant, while the rate and extent of hyphal development up to 5 h were normal. Therefore, we provide evidence that Cpp1p represses hyphal gene expression by acting through a Cek1p-independent mechanism. SAP4-6 and HYR1 transcripts were undetectable in a null mutant of another key regulator of filamentation, Efg1p; thus, Efg1p and Cpp1p oppose each other during the expression of these genes in hyphal forms.